2021
DOI: 10.1186/s12905-021-01532-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and management practices of primary dysmenorrhea among young females

Abstract: Background Primary dysmenorrhea (PD) is one of the most common gynecological conditions among young females, which has a significant negative impact on health-related quality of life and productivity. Despite its high prevalence, the evidence is limited regarding the management-seeking practices and its perceived effectiveness among females with PD. Methods This is a cross-sectional study conducted among 550 female students in six universities acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
4
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 57 publications
6
76
4
7
Order By: Relevance
“…Inappropriate counseling can be viewed as an ethical dispute, where some pharmacists demonstrate their preference for financial gain while violating the patient’s beneficence. This malpractice possesses significant consequences on the patient’s health, profession, reputation, and also the healthcare system [ 44 , 45 ]. Studies have shown that pharmacists, who provided quality pharmaceutical services, had clarified the misunderstandings about COVID-19, improved patient’s health outcomes, reduced the risk for severe disease, prevented virus transmission, and subsequently decreased healthcare expenditures [ 34 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate counseling can be viewed as an ethical dispute, where some pharmacists demonstrate their preference for financial gain while violating the patient’s beneficence. This malpractice possesses significant consequences on the patient’s health, profession, reputation, and also the healthcare system [ 44 , 45 ]. Studies have shown that pharmacists, who provided quality pharmaceutical services, had clarified the misunderstandings about COVID-19, improved patient’s health outcomes, reduced the risk for severe disease, prevented virus transmission, and subsequently decreased healthcare expenditures [ 34 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier review reported the prevalence of dysmenorrhea varying between 67% and 90% in women 17–24 years old [ 20 ]. The high prevalence of PD was also found in female students [ 21 , 22 ]. The MDOT study revealed an up to 93% prevalence rate of PD in Australian senior high school girls [ 21 ], while over 80% universities girl students were reported with PD in Lebanon [ 22 ].…”
Section: Introductionmentioning
confidence: 98%
“…According to the presence or absence of pathological pelvic diseases, dysmenorrhea can be divided into primary dysmenorrhea and secondary dysmenorrhea [ 29 ]. At present, the main treatment of dysmenorrhea is nonsteroidal anti-inflammatory drugs or oral contraceptives; however, these medicines exert adverse effects on metabolism and the digestive system [ 30 ]. TCM has proven to be associated with fewer adverse effects and to have a more remarkable curative effect on dysmenorrhea [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%